We, The Drowned - Jensen, Carsten (London Vintage Books, 2011)
In 1848 a motley crew of Danish sailors sets sail from the small island town of Marstal to fight the Germans. Spanning four generations, two world wars and a hundred years, We, The Drowned is an epic tale of adventure, ruthlessness and passion.
Keywords: Sailing -- Seafaring life